Assessment of Chlamydia trachomatis testing in Sweden 2016–2023 and the incidence of associated complications - Westborg, Siri; Elfving, Karin; Lindroth, Ylva; Stark, Lisa; Gullsby, Karolina; Gylfe, Åsa; Herrmann, Björn (Infectious Diseases, 2025)
Background: This study aimed to assess chlamydia diagnostics in different clinic types, including internet-based self-sampling (IBSS). Furthermore, we investigated the incidence of chlamydia-associated complications. Methods: Data on Chlamydia trachomatis (CT) testing were retrieved from six healthcare regions in the years 2016–2023 across different categories of testing facilities. National data on CT diagnostics and number of PID, ectopic pregnancy and infertility cases were obtained from Swedish health authorities. Results: The number of CT cases detected through IBSS increased by 85% from 2016 (n = 1967) to 2023 (n = 3644) when it accounted for 43% of all cases. The proportion of CT-positive individuals of all tested persons was similar for IBSS (7.0–8.5% per year); STI clinics (8.5–9.9%) and youth clinics (9.7–10.9%). In contrast, gynaecology clinics had a low proportion of CT-positive individuals (1.8–2.3%), and primary healthcare clinics a decreasing proportion (2016: 4.8%; 2023: 3.0%). For women in Sweden aged 15–39 years, there was a 33% decrease in detected CT cases from 2008 to 2022 (1577–1048 cases/100,000 women) while PID rates decreased by 63% from 2008 to 2022 (224–83 cases/100,000 women). Conclusions: IBSS has become the most important CT case detector in Sweden. Primary care and gynaecology clinics have low positivity rates. The decrease in PID rates may be due to generous CT testing, although other explanations are possible. Considering the low positivity rates in some clinic types and that asymptomatic CT cases have a low PID rate a reduced testing may be justified.
Keywords: Chlamydia trachomatis; diagnostic screening programs; health impact assessment; pelvic inflammatory disease; Sweden